Introduction to parallel computing : [a practical guide with examples in C] - Petersen, W. P. (Wesley P.) (Oxford texts in applied and engineering mathematics ;, 2004)
This text is a practical student guide to scientific computing on parallel computers, based on the authors' lectures at ETH Zurich. Aimed at advanced undergraduate and graduate students in applied mathematics, computer science, and engineering, subjects covered include linear algebra, fast Fourier transform, and Monte-Carlo simulations, including examples in C and, in some cases, Fortran. This book is also ideal for practitioners and programmers. - ;In the last few years, courses on parallel computation have been developed and offered in many institutions in the UK, Europe and US as a recognit.